Investigating the Effect of Corporate Logo Determinants on Corporate Image, Based on Consumer Perception: Conceptual Paper - Okechukwu, Worlu; Mohd Rashid, Sabrina; Shaari, Nassiriah (2018)
Organizations around the world have extensively focus in creating a favourable corporate logo that will represent their corporate image in the mind of the consumers and maintain competitive advantage. The effect of corporate logo on the corporate image has been given little attention in the marketing literature and has been barely researched in the emerging market. The objective of this study is to investigate on the effect of corporate logo determinants on the corporate image specifically in the Malaysian mobile service provider based on consumer perception. Quantitative method of electronic questionnaire was used to collect the data from the consumers of two mobile phone service providers in the Northern Region of Peninsular Malaysian. SPSS 20.0 was used to analysis the data. The findings of this research hope to answer the research questions and reach the research objective and extend the aspect of corporate logo and corporate image into mobile phone service provider in the Malaysian context..